PENGARUH MEDIA PEMBELAJARAN CANVA BERBANTUAN EDUCAPLAY TERHADAP PENINGKATAN MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V DI SD GMIT OEPURA - Shalomita L. C. Puling; Taty R. Koroh; Markus Sampe (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Pancasila Education is a subject that is starting to be forgotten. Many students do not focus and respond to teachers during learning, thus affecting students' motivation and learning outcomes. The purpose of this paper is to explain the effect of Canva learning media assisted by Educaplay on students' motivation and learning outcomes in Pancasila education learning in Grade V at SD GMIT Oepura. The research is a quantitative research with a quasi-experimental approach and a Nonequivalent Group Design. The research instruments are in the form of questionnaires, test questions, and observation sheets. The population of the study was all grade V students at SD GMIT Oepura totaling 43 students. The sampling technique with total sampling until a sample of 43 was obtained. The data analysis technique in this study was descriptive analysis and bivariate Paired sample t test and Independent sample t test. The results of the study showed that hypothesis testing with the paired sample t test had a difference in the average learning motivation of students after using Canva learning media assisted by Educaplay in the Pancasila Education subject. The test results also showed that there was a difference between the level of learning outcomes before and after being given Canva learning media assisted by Educaplay. The independent sample t-test showed that there was an influence of canva learning media assisted by educaplay on student learning motivation in the control and experimental classes. The results of the statistical test also showed that there was an influence of canva learning media assisted by educaplay on the learning outcomes of grade V elementary school students at SD GMIT Oepura.